Evaluating the Nigerian prosperity gospel as a mixed ideology - Omavuebe, Augustine I. (Missiology, 2021)
There are two popular suggestions as to how the prosperity gospel emerged in Nigeria. The first school of thought posits that the phenomenon of the prosperity gospel was exclusively an American ideology imported into Nigeria, while the second view holds that it was entirely an African ideology nurtured with African ingredients and popularised on African soil. There has been little literature that has actively and adequately explored the Nigerian prosperity gospel as a combination of the American prosperity gospel and the Nigerian Pentecostal revivalism. Therefore, to fill this gap in the literature, this article suggests that the Nigerian prosperity gospel is a joint theology with elements of the American prosperity gospel ideology, which has its origins in the American New Thought movement, and the Nigerian Pentecostal revivalism, which has its origins in the Nigerian indigenous Pentecostal movement. This attempt employs a historical approach. In this vein, the narrative explores related literature about the prosperity gospel in Nigeria and offers a radical shift from the popular views that solely attribute the emergence of prosperity gospel ideology to either the Nigerian Indigenous Pentecostal revivalism or the American prosperity theology.
free